H09 The Depression Phenotype In Huntington's Disease. (17th September 2014) - De Souza, J; Gordon-Smith, K; Jones, L; Rickards, H
Abstract : Background: Depression is one of the most common psychiatric disorders in individuals with Huntington's disease (HD) and negatively impacts quality of life, functional ability and cognitive performance. However, reported prevalence rates vary greatly and little is known about the presentation of depression in HD. Aims: To determine the lifetime prevalence of DSM-IV depressive disorders in a sample of unrelated individuals with HD, and to compare the depression phenotype in this HD sample and individuals with unipolar depression without HD. Methods: Fifty unrelated individuals gene positive for HD were assessed for lifetime psychopathology using the Schedules for Clinical Assessment in Neuropsychiatry (SCAN) and best-estimate lifetime DSM-IV diagnosis and key illness course features were determined. 784 individuals with DSM-IV major recurrent depressive disorder (MDDR) and no HD, who were assessed using the same methods in an ongoing genetic epidemiology study, formed the comparison group. Results: Twenty-eight individuals (56%) in the HD sample had a lifetime diagnosis of a DSM-IV depressive disorder and 12 individuals (24%) had a lifetime diagnosis of MDDR. Compared to the non-HD sample, individuals with HD and MDDR were significantly more likely to have a later median age at onset of depression (p = 0.001) and a higher level of functioning during their worst episode of depression (p = 0.006) and were significantly less likely to experience diurnal variation (p = 0.008), middle insomnia (p = 0.036) and increased appetite (p = 0.043) during their worst episode of depression. Conclusions: The prevalence of lifetime DSM-IV depressive disorders in HD is up to four times higher than in the general population and the depression phenotype may be less severe with a higher age of onset.